Blue Emissive fac/mer‐Iridium (III) NHC Carbene Complexes and their Application in OLEDs. Issue 8 (10th February 2021) - Idris, Muazzam; Kapper, Savannah C.; Tadle, Abegail C.; Batagoda, Thilini; Muthiah Ravinson, Daniel Sylvinson; Abimbola, Opeoluwa; Djurovich, Peter I.; Kim, Jongchan; Coburn, Caleb; Forrest, Stephen R.; Thompson, Mark E.
Abstract: The photophysical and electrochemical properties of N‐heterocyclic carbene complexes of Iridium (III) (Ir(C ^ C:)3, where C ^ C: = N‐phenyl, N‐methyl‐pyrazinoimidazol‐2‐yl (pmpz), N, N‐di‐p‐tolyl‐pyrazinoimidazol‐2‐yl (tpz)) are reported. Facial and meridional isomers of Ir(pmpz)3 are prepared, but only the facial isomer can be isolated for Ir(tpz)3 . The fac ‐Ir(pmpz)3 and fac ‐Ir(tpz)3 complexes have emission maxima at 465 nm in polystyrene, whereas the emission maximum of mer ‐Ir(pmpz)3 is redshifted to 495 nm. The emission energies and photoluminescent quantum yield (ΦPL ) in solution decrease on going from nonpolar to polar solvents; however, all the complexes are efficient emitters in polystyrene at room temperature (ΦPL = 88–96%) and 77 K. Blue phosphorescent organic light emitting diodes employing fac ‐Ir(tpz)3 as an emissive dopant achieves a high external electroluminescence efficiency (≈18 ± 1%) and brightness (29 000 cd m −2 ) at low current density. Abstract : The photophysical and electrochemical properties of three N‐heterocyclic carbene complexes of Iridium (III) are reported. The complexes phosphoresce in the blue with high photoluminescent quantum yield (ΦPL = 88–96%). Blue phosphorescent organic light emitting diodes employing one of the complexes as a emissive dopant achieve a high external electroluminescence efficiency (≈18 ± 1%) and brightness (29 000 cd m −2 ).